Pagtuligsa, pagbawas at muling sipat kay Rizal bilang bayani - Ocampo, Nilo S. (2015)
Accessed online through this link: https://journals.upd.edu.ph/index.php/lagda/article/view/5183/4655
Keywords: Rizal, Jose ,1861-1896; Heroes; Literary criticism